Chronic Otitis Media Resulting in Aortic Valve Replacement: A Case Report - Adem Guler; Mehmet Ali-Sahin; Fahri Gurkan-Yesil; Uzeyir Yildizoglu; Sait Demirkol; Mehmet Arslan (Journal of Tehran University Heart Center, 2015)
The bicuspid aortic valve is known to be the most common congenital cardiac malformation, with an approximate incidence rate of 1-2% in the general population. Most patients are unaware of the disease until the onset of infective endocarditis, which is a life-threatening complication that may affect a heart valve or other cardiac structures at the site of endothelial damage. A 22-year-old man presented to our internal medicine clinic with a complaint of acute onset dyspnea and fatigue. His body temperature was 38 °C. A diastolic murmur was detected at the right sternal border. Two-dimensional transthoracic echocardiography revealed severe aortic insufficiency, and two-dimensional transesophageal echocardiography showed that the aortic valve was bicuspid. There was also a flail lesion extending the left ventricular outflow tract, resulting in pathological coaptation and severe aortic insufficiency. The patient was referred to our cardiovascular department for surgery. We herein present this case of a bicuspid aortic valve complicated by infective endocarditis due to the underlying disease of chronic otitis media related to a rare pathogen: Alloiococcus otitidis. The patient underwent a successful aortic valve replacement surgery due to aortic insufficiency following infective endocarditis. He was discharged on the 16th postoperative day in good condition.